Word Production (Al-Tawlīd Al-Luġawy) in Arabic: Causes and Types - Uki Sukiman (IJAS: Indonesian Journal of Arabic Studies, 2021)
Word Production (Called in Arabic by Al-Tawlīd Al-Luġawy) which means inventing new words is one of development of language phenomenon that happens in any languages including Arabic. This phenomenon is a demand of condition that one language is not capable of expressing ideas and emotions and has something to do with communication with non-speaker or other languages. Thus, a language can influence and be influenced. This paper tried to uncover reasons and theories using comparative study so that it is clear for Arabic language researchers to use tawlid in their research. The writer found eight reasons why neology emerged, which are development of civilization, friction between Arab and Non-Arab, administration system after Islamic expansion, translation process from Greek into Arabic, social and political demands, the beauty of expression, and inventing new scientific terms, while Ibrahim Murad stated five theories about neology: phonetic neology, morphological neology, semantic neology, spontaneous neology, and borrowing neology; as Nasruddin suggested five theories such as transfer of meaning, derivation, derivation from Arabization (mu’rab) or loanwords (dakhil), taulid form coinase and structure, metaphor neology, and meaning expansion.التوليد بمعنى إحداث كلمة جديدة  مظهر من مظاهر تطوراللغات منها اللغة العربية.تكون هذه المظاهر من متطلبات الأحوال من عدم كفائة اللغة فى تعبير أفكار صاحب اللغة و مشاعرهم خاصة و نتيجة من تعاملهم مع الآخرين فأثروا وتأثّروا. اهتمّ كثير من علماء اللغة بهذه المظاهر و بحثوا فى أسبابها و دواعىها بل جعلوا قواعدها. فهذه المقالة تعرض جهدهم فى هذا المجال فى اكتشاف تلك أسباب والقواعد بمنهج مقارنة حتى تكون واضحة لمحببي اللغة العربية راجيا استعمالهمم فى بحوثهم و مقالتهم.وجد الكاتب ثمانىة أسباب لظهور التوليد فى اللغة العربية وهي التطور الـحضاري، والاحتكاك بين العرب الأعجم، والـحاجة الـملحة، والنظام الإداري عند العرب بعد الفتوحات الإسلامية، وعملية ترجمة العلوم اليونانية إلى اللغة العربية، والدعاية السياسية والاقتصادية، وجمال التعبير، ووضع الـمصطلحات العلميةكما وجد ابراهيم مراد الذي قدم خمس قواعيد يعني التوليد الصوتي، التوليد الصرفي، التوليد الدلالي، التوليد بالارتجال، التوليد بالانقراضحيث لكل منها فصول كما قدم نصر الدين ست قواعيد وهي انتقال الـمعنى، والاشتقاق، والاشتقاق من الـمعرب أو الدخيل،والتوليد بالنحت والتركيب،والتوليد الـمجازي، والتوسع.